Looking at crime: communities and physical spaces. A research project about crime in historic center of Porto - Nunes, L. (2020)
Poster apresentado no III OPVC International Congress - LookCrim International Congress ‘Violence, Crime and Security’: Justice, (In)Security and Mediatization (Porto, Portugal)